Investigating the influence of novel drying methods on sweet potato (Ipomoea batatas L.): kinetics, energy consumption, color, and microstructure - Hashim, Norhashila; Abdan, Khalina; Janius, Rimfiel; Chen, Guangnan; Onwude, Daniel I. (Wiley Periodicals, 2018)
This study investigated the drying kinetics, specific energy consumption (SEC), color, and microstructural changes of sweet potato (Ipomoea batatas L.) based on experimental set‐up of convective hot‐air drying (CHAD), infrared drying (IRD), and combined infrared and convective‐hot‐air drying (IR‐CHAD). The experiments were carried out at three air temperatures (50, 60 and 70 °C) and two IR intensities (1,100 and 1,400 W/m2) for sweet potato slices of 4 and 6 mm, respectively. The experimental results showed that the drying kinetics and mass transfer characteristic were significantly affected by drying air temperature, IR intensity, and thickness of the product. Combined IR‐CHAD provided a higher drying rate with the shortest drying time when compared with CHAD and IRD. The IRD resulted in the lowest SEC values. The combined IR‐CHAD resulted in 69.34–85.59% reduction in the SEC of CHAD. For combined IR‐CHAD, an increase in the IR intensity at each temperature and slice thickness caused a decrease in the total SEC value. Dried sweet potato slices using CHAD and IR1‐CHAD at intensity of 1,100 W/m2 showed the best color attributes. Combined IR‐CHAD proved to be a very efficient drying method for the drying sweet potato and can be used for both industrial and commercial purposes.